2016
DOI: 10.1080/01904167.2016.1187750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen application on seed yield, pod and seed characteristics of okra

Abstract: Four okra cultivars (Abelmoschus esculentus [L.] Moench) were cultivated for two growing periods at nitrogen (N) application rates of 150, 300 and 450 mg N L 1 . There was no effect of N on pod size (length and diameter) or on the number of seeds per pod and seed size (mean 1000 seed weight), all these characteristics of which related to the genotype. High N application (450 mg N L 1 ), increased the seed yield of the cultivar with the lowest flower induction (Boyiatiou), but only in experiment 2. In Veloudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This might be due to the fact that the enhanced food materials translocated towards the site of new pod formation and development. The results are in accordance with the findings of Mohammadi et al, (2015), Moniruzzaman and Quamruzzaman (2009), Khan and Jaiswal (1988) and Grewal et al, (1972).…”
Section: Influence Of Fruit Positions and Fruit Retention Loads On Growth Parameterssupporting
confidence: 92%
“…This might be due to the fact that the enhanced food materials translocated towards the site of new pod formation and development. The results are in accordance with the findings of Mohammadi et al, (2015), Moniruzzaman and Quamruzzaman (2009), Khan and Jaiswal (1988) and Grewal et al, (1972).…”
Section: Influence Of Fruit Positions and Fruit Retention Loads On Growth Parameterssupporting
confidence: 92%
“…From the results of the study, it is apparently clear that supply of N sources played a significant role in the vegetative growth of alder even in degraded coal mine soil. There is evident from the previous study that N must be required for the growth and development of plant, and it can stimulate photosynthesis in plants by making more area available for photosynthesis process, and subsequently increase assimilation [6,7]. Therefore, N fertilizer and N fixation in our study showed a significant increase in the growth parameters of alder in coal mine soil.…”
Section: ) T0 = Control (No Source Of N Was Given On the Soil) T1mentioning
confidence: 49%
“…N is one of the most important nutrients required for plant growth and development [6]. Previous studies have shown that N has a significant role in increasing the vegetative growth of plant and can also increase photosynthesis and assimilation in plants [6,7]. Regular application of nitrogenous and other nutrient fertilizers to the soil is a good approach to maintain the sustainability and healthy growth of vegetation in coal mine land [8,9].…”
Section: Introductionmentioning
confidence: 99%